the Implementation Of Word Wizard Game In Learning Vocabulary - Tria Auliani, Fitriah & Rahmi Fhonna (JADEs Journal of Academia in English Education, 2022)
This research was conducted to discover the student's interest in learning vocabulary and focused on investigating student's perspectives on the implementation of the game in learning vocabulary. This research contain one research question namely how are the student's responses toward the use of Word Wizard game in learning vocabulary. The research employed a qualitative narrative to investigate a student's responses in learning English vocabulary using Word Wizard game. The participants of this research were thirteen students of grade one SMP Terpadu Semayoen Nusantara in Bener Meriah regency. Further, the researcher conducted observation and interview as a research instrument. The interview addressed some questions that were leading the students to be interested in responding the questions related to learning English vocabulary with the Word Wizard game. The interview was then transcribed to analysis this study. Thematic analysis was then used to analyze the student's interest from the script of the interview. The result showed that the students were very excited and interested in learning English vocabulary with Word Wizard game. The game helped students to remember and to find new words in English. The students also assert that learning English vocabulary by using Word Wizard game was much easier and they can be more enthusiastic. This media had a positive impact on students in learning English vocabulary.